2021
DOI: 10.3389/fimmu.2021.631483
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive Genomic Profiling of Rare Tumors in China: Routes to Immunotherapy

Abstract: Treatment options for rare tumors are limited, and comprehensive genomic profiling may provide useful information for novel treatment strategies and improving outcomes. The aim of this study is to explore the treatment opportunities of patients with rare tumors using immune checkpoint inhibitors (ICIs) that have already been approved for routine treatment of common tumors. We collected immunotherapy-related indicators data from a total of 852 rare tumor patients from across China, including 136 programmed cell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 56 publications
0
4
0
Order By: Relevance
“…All samples were tested by NGS in the Geneplus-Beijing laboratory, which is accredited by American College of Pathologists ( Sun et al, 2019 ; Wang et al, 2020 ; Zhuo et al, 2020 ; Wang et al, 2021 ). Briefly, all tissue samples were hematoxylin-eosin stained and reviewed to ensure a minimum of 20% tumor cells.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…All samples were tested by NGS in the Geneplus-Beijing laboratory, which is accredited by American College of Pathologists ( Sun et al, 2019 ; Wang et al, 2020 ; Zhuo et al, 2020 ; Wang et al, 2021 ). Briefly, all tissue samples were hematoxylin-eosin stained and reviewed to ensure a minimum of 20% tumor cells.…”
Section: Methodsmentioning
confidence: 99%
“…Our team has previously studied the genomic profiling of rare tumors in China, which indicated that employing targeted therapy and immunotherapy in rare tumors is highly feasible ( Wang et al, 2020 ; Wang et al, 2021 ). However, the molecular landscape of KRAS mutation in rare tumors has not been studied.…”
Section: Introductionmentioning
confidence: 99%
“…In a cross-sectional study involving 54 cancer patients undergoing anti-PD-1 or anti-PD-L1 therapy and 50 healthy controls, there was a statistically significant rise in APA observed among these patients 126 . Furthermore, the impact of the host's germline on the response to ICI therapy is worth exploring, and human leukocyte antigen class I (HLA-I) serves as a valuable prognostic biomarker for this purpose 127 . CD8 + T cells play a major role in the antitumor activity of ICIs and are required to present tumor antigens via HLA-I 128 .…”
Section: Immunotherapy-related Adverse Eventsmentioning
confidence: 99%
“…In recent decades, great progress has been made in immunotherapy for advanced cancer leading to a substantial survival benefit in multiple solid tumors, including gastric, liver, NSCLC, etc. We investigated the expression levels of programmed cell death ligand-1 (PD-L1) in 852 rare tumor patients, finding a prevalence of 47.8% positivity, which is higher than the prevalence found in common cancers with approved indications for immunotherapy (Wang et al, 2021). Both MSI and TMB are recognized predictive biomarkers for response to immune checkpoint inhibitors by the FDA in multiple solid tumors.…”
Section: Potential Therapeutic Targets For Rare Tumors In Chinamentioning
confidence: 99%